2009
DOI: 10.1007/s11368-009-0058-0
|View full text |Cite
|
Sign up to set email alerts
|

Using earthworm avoidance behaviour to assess the toxicity of formulated herbicides and their active ingredients on natural soils

Abstract: Background, aim, and scope Soil quality has been threatened by intensive agricultural practises, namely those relying on the application of pesticides, such as herbicides. Among the non-target terrestrial organisms exposed to such scenarios, earthworms are key ecological receptors widely used in ecotoxicological studies. As such, this work aims to assess the effects of two herbicide active ingredients (a.i.)-sulcotrione and penoxsulam-and their respective commercial formulations-MIKADO® and VIPER® (referred as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Li et al (2015) reported that at concentration of 0.1 mg/kg of Enrofloxacin, E. fetida showed attraction behavior. Marques et al (2009) found that E. Andrei showed attraction behavior at concentration of 31.7 mg/kg of formulated herbicide Mikado (a.i. is sulcotrione).…”
Section: Resultsmentioning
confidence: 99%
“…Li et al (2015) reported that at concentration of 0.1 mg/kg of Enrofloxacin, E. fetida showed attraction behavior. Marques et al (2009) found that E. Andrei showed attraction behavior at concentration of 31.7 mg/kg of formulated herbicide Mikado (a.i. is sulcotrione).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, the same authors found higher toxicity of the formulated carbofuran compared to the pure substance for the tropical earthworm Perionyx excavatus [15]. The avoidance behavior of E. andrei was also found to be stronger toward soil contaminated with a commercial formulation of the herbicide penoxsulam compared with the pure chemical [39]. Commercial formulations probably contain other chemical agents that could either enhance the toxicity of the pesticide or that are themselves toxic.…”
Section: Carbofuran Toxicity To Soil Organismsmentioning
confidence: 91%
“…The presence of toxic adjuvants in commercial pesticide formulations may also increase toxicity. Marques et al (2009) found that the behaviour of the earthworm Esenia andrei was affected under VIPER Ò exposures in soils, the formulated product being even more repulsive for E. andrei than the active ingredients benzofenap and clomazone. In our study, predicted TU, conductivity and suspended solids were at the upper tolerance range of the studied species (Barata et al 2006(Barata et al , 2009 and other unmeasured pesticides could also be present (Kuster et al 2008).…”
Section: Ecotoxicological Responsesmentioning
confidence: 99%